2019
DOI: 10.1016/j.jfma.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical behavior and management of three types of renal angiomyolipomas

Abstract: A larger tumor size, younger patient's age and higher BMI value correlated with a higher risk of tumor hemorrhage. For tumor sizes less than 7.35 cm, we recommend active surveillance or TAE for hemorrhage prevention. We also suggest that surgical management should be considered for patients with tumors larger than 7.35 cm, symptomatic and progressive AML, or suspicious EAML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 41 publications
0
31
1
4
Order By: Relevance
“…During standard ultrasound follow-up of our childhood cancer survivors (CCSs), sporadic renal angiomyolipomas without histological confirmation (SAMLs) were consistently detected. SAMLs are uncommon benign tumors most often affecting the kidney composed of blood vessels, smooth muscles, and adipose tissue in varying proportions 1–3 and are incidentally detected in older people by diagnostic imaging performed for various medical reasons. 4 , 5 They usually present as unilateral single lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During standard ultrasound follow-up of our childhood cancer survivors (CCSs), sporadic renal angiomyolipomas without histological confirmation (SAMLs) were consistently detected. SAMLs are uncommon benign tumors most often affecting the kidney composed of blood vessels, smooth muscles, and adipose tissue in varying proportions 1–3 and are incidentally detected in older people by diagnostic imaging performed for various medical reasons. 4 , 5 They usually present as unilateral single lesions.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 They usually present as unilateral single lesions. 1–3 The prevalence in the general population is reported to be 0.1–0.44%. 4 , 5 Previous studies in non-cancer populations reported a higher SAML prevalence in women, and the effect of sex hormones was considered.…”
Section: Introductionmentioning
confidence: 99%
“…Güncel bir çalışmada kanama görülen AML' lerin ortalama boyutu 8 cm, kanama görülmeyen olguların ortalama boyutu 4.1 cm olarak bulunmuş, kanama tahmini için sınır değeri 7.35 cm olarak bildirilmiştir (3). Ayrıca başka bir çalışmada kanayan tümörler ortalama 11.4 cm, kanamayanlar 5 cm olarak bulunmuştur (16).…”
Section: Takip Ve Kanamaunclassified
“…Bu çalışmada ise 3 olguda kanama saptanmış olup ortalama tümör boyutu 220 mm (min-maks: 84-363 mm)' dir. Güncel bir çalışmada sporadik olarak saptanan AML' lerin ortalama boyutu 47 mm olarak bulunmuştur (3). Bu çalışmada ortalama tümör boyutu 39.2 mm (5-363 mm)' dir.…”
Section: Takip Ve Kanamaunclassified
See 1 more Smart Citation